180k views
0 votes
Is this the correct first step?

Is this the correct first step?-example-1
User NorthGuard
by
4.9k points

1 Answer

5 votes

Answer:

The solution is

Explanation:

No


8^3^x^-^4 =
2^2^x^+^9


2^3^(^3^x^-^4^)=
2^2^x^+^9

multiply 3 with 3x - 4 in the power then we get


2^9^x^-^1^2=
2^2^x^+^9

hence 2 is same so we compare the power values then we get

9x-12 =2x +9

9x - 2x = 9+12

7x = 21

divide by 7 on both sides we get

7x / 7 = 21 / 7

x = 3

User Nefertari
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.